Endovascular and Open Repair of Abdominal Aortic Aneurysm - Schmitz-Rixen, Thomas (Dtsch Arztebl Int, 2020)
BACKGROUND: This review presents the surgical indications, surgical procedures, and results in the treatment of asymptomatic and ruptured abdominal aortic aneurysms (AAA). METHODS: An updated search of the literature on screening, diagnosis, treatment, and follow-up of AAA, based on the German clinical practice guideline published in 2018. RESULTS: Surgery is indicated in men with an asymptomatic AAA ≥ 5.5 cm and in women, ≥ 5.0 cm. The indication in men is based on four randomized trials, while in women the data are not conclusive. The majority of patients with AAA (around 80%) meanwhile receive endovascular treatment (endovascular aortic repair, EVAR). Open surgery (open aneurysm repair, OAR) is reserved for patients with longer life expectancy and lower morbidity. The pooled 30-day mortality is 1.16% (95% confidence interval [0.92; 1.39]) following EVAR, 3.27% [2.7; 3.83] after OAR. Women have higher operative/interventional mortality than men (odds ratio 1.67%). The mortality for ruptured AAA is extremely high: around 80% of women and 70% of men die after AAA rupture. Ruptured AAA should, if possible, be treated via the endovascular approach, ideally with the patient under local anesthesia. Treatment at specialized centers guarantees the required expertise and infrastructure. Long-term periodic monitoring by mean of imaging (duplex sonography, plus computed tomography if needed) is essential, particularly following EVAR, to detect and (if appropriate) treat endoleaks, to document stable diameter of the eliminated aneurysmal sac, and to determine whether reintervention is necessary (long-term reintervention rate circa 18%). CONCLUSION: Vascular surgery now offers a high degree of safety in the treatment of patients with asymptomatic AAA. Endovascular intervention is preferred.